2008
DOI: 10.1186/cc6802
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of tracheostomy decannulation: an international survey

Abstract: Background Although tracheostomy is probably the most common surgical procedure performed on critically ill patients, it is unknown when a tracheostomy tube can be safely removed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
1
16

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(152 citation statements)
references
References 31 publications
8
127
1
16
Order By: Relevance
“…With a specialized service, decisionmaking is centralized to those with the required expertise, which leads to more consistent evidence-based management. However, even among those clinicians with experience in tracheostomy care, Stelfox and colleagues 6 reported that significant variability in opinions existed concerning the appropriate timing for decannulation. This is true in part because guidelines for tracheostomy management do not exist.…”
Section: Resultsmentioning
confidence: 99%
“…With a specialized service, decisionmaking is centralized to those with the required expertise, which leads to more consistent evidence-based management. However, even among those clinicians with experience in tracheostomy care, Stelfox and colleagues 6 reported that significant variability in opinions existed concerning the appropriate timing for decannulation. This is true in part because guidelines for tracheostomy management do not exist.…”
Section: Resultsmentioning
confidence: 99%
“…This outcome is considered satisfactory, because only 2 patients required reintubation and those patients who were not recommended for decannulation were transferred to a convalescent hospital and were reevaluated at a later date. Predictors of successful decannulation include level of consciousness, secretions, oxygenation, 19 and the ability to produce a vigorous cough. 20 Irrespective of the method used to measure cough strength, a consistent association between cough and extubation/decannulation outcomes has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Hay pocos estudios que expresen la circunstancia idónea para decanular y están basados fundamentalmente en la experiencia personal de sus autores [42]. En base a la literatura publicada [8,13,27,37,[43][44][45][46][47], aplicamos actualmente el protocolo de la Tabla 2, junto a la evaluación fibroendoscópica ya descrita [28]. Pero nuestra mejor referencia es la que obtenemos de la evaluación continuada, de las posibles emergencias y del permanente contacto con el paciente.…”
Section: Discussionunclassified